The Impact of Using DUOLINGO Application on Students' English Learning Motivation - Suryanto, Bradhiansyah Tri; Hasaniyah, Nikmatul; Mumimah, Humairotul; Hasanah, Ulfatun; Qiftiyah, Nor; Rifka, Rifka; Surur, Nikmahus; Syifaturrohman, Syifaturrohman; Ulfiani, Ery Susanti (International Journal of English Education and Linguistics (IJoEEL), 2024)
The application of technology in English language education is increasingly widespread, one of which is through the Duolingo app. This study aims to evaluate the impact of using the Duolingo app on students' motivation in learning English as well as identify the specific factors that contribute to such motivation. The research method used was a mixed approach, combining quantitative and qualitative. Quantitative data was collected through a structured questionnaire with a Likert scale to measure students' motivation and contributing factors. Qualitative data was obtained through focus group discussions (FGDs) to explore students' experiences and perceptions in depth. The results showed that the Duolingo app significantly increased students' motivation in learning English. Findings from the questionnaire indicated that 53.3% of respondents strongly agreed that Duolingo was effective in increasing their motivation, while 46.7% agreed with the statement. The focus group discussion corroborated these findings by emphasising the role of gamification features, such as points and badges, as well as self-paced learning features in making the learning process more enjoyable and improving English confidence and comprehension. The findings are consistent with previous research highlighting the effectiveness of gamification and self-paced learning features and make a novel contribution by exploring the overall impact of different app features. Limitations of this study include the limited sample size and reliance on self-report data, which may affect the generalisability of the results. Future research is recommended to use a larger and more diverse sample and more varied data collection methods, including direct observation and in-depth interviews. Future research could also explore the long-term effects of using Duolingo and the differences in its impact based on students' educational background or initial ability level. It is hoped that these recommendations will provide a deeper understanding of the effectiveness of this app in the broader context of English language education.